Pemberdayaan Masyarakat Diversifikasi Produk Olahan Buah Balakka Terintegrasi Smart Production Berbasis IOT - Lubis, Mustopa Husein; tanjung, akhir abadi; Andrianto, richi - (STMIK Royal, 2024)
Utilization of balakka fruit is a typical fruit of North Padang Lawas Regency which can be used for superior preparations such as balakka fruit dodol. So far, balakka fruit has only been used for balakka syrup and juice. For this reason, community service was created in innovating balakka fruit by processing balakka fruit into balakka fruit dodol based on smart production. The urgency is expected to be used as an effective and efficient solution to increase people's knowledge and skills in processing balakka fruit. This community service activity aims to carry out dissemination and training on smart production-based balakka fruit dodol processing in the community of Padang Garugur Village, North Padang Lawas Regency, so that the community can be more productive with a technological approach. It is hoped that the results of the research will increase community knowledge and skills in processing balakka fruit into dodol based on smart production so that this service activity directly influences community productivity.. Keywords: Balakka Fruit; Product; Smart Production; IOT